Biologycal activity of Urtica cannabina L. extract - K. V. Gubin; A. V. Sen'kova; M. A. Khanina; T. A. Ageyeva (Бюллетень сибирской медицины, 2011)
The dry Urtica cannabina L. extract, containing complex of biologically active materials in different regimes introduced to mice with conducting poly-chemotherapy for the purpose of reduction in its toxicity. As a result a pathomorphological study of the liver of mice it was proven that the extract of U. cannabina decreases the manifestation of the toxic action (dystrophia and the necrosis of the hepatocytes) of poly-chemotherapy on a liver. Most effective is the regime of extract introduction before and after poly-chemotherapy.